Inherited, Versus Acquired, Measles IgG-antibodies after Measles Vaccination Among Infants in Diyala /Iraq - Abdul, Salwa Sh (Iraqi Journal of Cancer and Medical Genetics, 2010)
Back-ground: In developing countries, measles is regarded as a serious problem and can only becombated by large-scale vaccination programs. The main known risk factor for primary vaccine failure is age at vaccination, due to persistence of maternal antibodies, which interferes with the success of measles immunization.Objectives: Identification of sero-prevalence rate of inherited measles IgG- antibodies among infants aged 9-12months, before measles vaccination. And assessment of acquired sero-conversion rate after inoculation of measles vaccine among those infants.Subjects and Methods: A cross –sectional study, was conducted in a selected primary health care centers in Diyala Province. The study sample included 117 infants (56 males & 61 females), aged 9-12 months, selected at a random during their routine vaccination, for the period extending from the 1st of February/2007 to the 31st January/2008. Anti measles IgG antibodies (Abs), were detected in the serum by Enzyme Linked Immuno-Sorbent Assay, using “Dade Behring” standard test kit.Results: The results revealed that the mean & geometric mean measles IgG Abs titers, before measlesvaccination were negative (cut off= 330mIU/ml-